Efektivitas Aromaterapi Lavender terhadap Kualitas Tidur Bayi - Failla shofa; Atun Wigati; Diah Andriani (Midwifery Care Journal, 2026)
Quality of a baby's sleep is an important aspect for physical growth, cognitive development, and emotional balance. Sleep disorders in babies are still common, with a global prevalence of 20-40%. Non-pharmacological efforts such as lavender aromatherapy are known to have sedative effects through the active components of linalool and linalyl acetate that act on the central nervous system to improve relaxation and sleep quality. Objective of the research was to determine the effectiveness of lavender aromatherapy on the quality of infant sleep at PKU Muhammadiyah Gubug Hospital. Methods of this study used a pre-experimental design with a pretest-posttest one group design approach. The population is all babies aged 3-12 months who are treated at PKU Muhammadiyah Gubug Hospital as many as 42 babies, and all of them are sampled using total sampling techniques. The intervention was in the form of inhalation of lavender aromatherapy one drop in a diffuser containing 100 ml of water for 15–20 minutes before bedtime, carried out once a day for three days. Sleep quality measurement was conducted using the Brief Infant Sleep Questionnaire (BISQ). The data were analyzed using the Wilcoxon test. The results of the study was the effectiveness of lavender aromatherapy on the quality of infant sleep at PKU Muhammadiyah Gubug Hospital is p value 0.000. Conclusion of the study was lavender aroma therapy can improve the quality of baby sleep.